Formula of success : the Singapore Airlines story. - Chua, Teow Tzing. (2009)
The world airline industry is a highly competitive, albeit lucrative, arena. In this environment, Singapore SIA has emerged as one of the role models of airline success story in recent aviation history. The research looks at the business environment in which the airline operates -in terms of the available opportunities and threats. SIA's impressive profitability record and the success factors that relate to her sustained profitability.